Clinical trajectories and impact of acute kidney disease after acute kidney injury in the intensive care unit: a 5-year single-centre cohort study. Issue 1 (3rd March 2022) - Orieux, Arthur; Prezelin-Reydit, Mathilde; Prevel, Renaud; Combe, Christian; Gruson, Didier; Boyer, Alexandre; Rubin, Sébastien
ABSTRACT: Background: Patients suffering from acute kidney injury(AKI) in the intensive care unit (ICU) can have various renal trajectories and outcomes. Aims were to assess the various clinical trajectories after AKI in the ICU and to determine risk factors for developing chronic kidney disease (CKD). Methods: We conducted a prospective 5-year follow-up study in a medical ICU at Bordeaux University Hospital (France). The patients who received invasive mechanical ventilation, catecholamine infusion or both and developed an AKI from September 2013 to May 2015 were included. In the Cox analysis, the violation of the proportional hazard assumption for AKD was handled using appropriate interaction terms with time, resulting in a time-dependent hazard ratio (HR). Results: A total of 232 patients were enrolled, with an age of 62 ± 16 years and a median follow-up of 52 days (interquartile range 6–1553). On day 7, 109/232 (47%) patients progressed to acute kidney disease (AKD) and 66/232 (28%) recovered. A linear trajectory (AKI, AKD to CKD) was followed by 44/63 (70%) of the CKD patients. The cumulative incidence of CKD was 30% [95% confidence interval (CI) 24–36] at the 5-year follow-up. In a multivariable Cox model, in the 6 months following AKI, the HR for CKD was higher in AKD patients [HR 29.2 (95% CI 8.5–100.7); P < 0.0001). After 6 months, the HR for CKD was 2.2 (95% CI 0.6–7.9; P = 0.21; n = 172 patients). Conclusion: There were several clinical trajectories of kidney disease after ICU-acquired AKI. CKD risk was higher in AKD patients only in the first 6 months. Lack of renal recovery rather than AKD per se was associated with the risk of CKD. Graphical Abstract: